Trading culture for development: assessing perceptions among rural agropastoral peoples in Tanzania. Issue 6 (18th August 2018) - Knapp, Eli J.; Hoffman, Tanner J.S.
ABSTRACT: Development in rural parts of Africa is strongly desired by local people. Other views expressed by local people towards outside development initiatives vary considerably. Some perceptions are negative, as development recipients view development as a destructive agent of change in the local culture. Despite the negative effects associated with development, this study documented a unanimous desire among a stratified random sample of 418 respondents for more development interventions. Two villages in south-central Tanzania were selected based upon their adjacent proximity to Ruaha National Park. Findings suggest that a capability framework is useful for exploring local perceptions to outside development assistance.